Utilization of Leaflet Health Promotion Media in Hospital Inpatient Rooms: A Qualitative Study - Aldo Prama Ananta; Novita Rany; Dewi Hayati Prabu (Viva Medika, 2024)
The implementation of Hospital Health Promotion (PKRS) in the inpatient rooms of Arifin Achmad Regional General Hospital faced several obstacles, causing the available PKRS leaflets to accumulate and go unread by patients and families. The purpose of this study was to identify problems, prioritize issues, and determine alternative solutions. The method used was qualitative with in-depth interviews, observation and document review. Problem prioritization was done qualitatively using the Urgency, Seriousness, Growth (USG) method. The study found 5 main problems in PKRS implementation: unavailability of needed infrastructure hindering PKRS activities, lack of utilization of leaflet health promotion media, suboptimal monitoring and evaluation of hospital health promotion management, no revision of standard operating procedures in the PKRS unit, and inactive monitoring and evaluation with several foundations and associations. USG analysis concluded the main issue was non-functioning leaflet media in inpatient rooms due to underutilization by nurses. Alternative solutions were adjusted to the problem elements: man, method, material, market, machine, money and environment